Impact Analysis of Missense Variants of Unknown Significance Using the TRPV4 Protein as a Model: A Study Guide - Ligia Silva Pondé Serra; Juliane da Silva Ferreira; Kamila de Oliveira e Silva; Sérgio Amorim de Alencar (New Visions in Biological Science Vol. 3, 2021)
The TRPV4 protein is a channel protein that acts as a calcium channel. This channel, which carries positively charged calcium atoms (calcium ions) across cell membranes, is found in many types of cells and tissues. Dysfunctions in this protein have been associated with several diseases such as: vascular stiffness, chronic asthma, dermatological pathologies such as psoriasis and rosacea; neuromuscular disease, progressive peripheral neuropathy and skeletal dysplasias. Among the possible causes of these dysfunctions, are the changes of a single nucleotide (SNVs) in the coding region of the TRPV4 gene that can affect the protein’s function. This study aims to analyze the possible impact of 29 variants of unknown significance (VUSs) identified in the TRPV4 gene. A total of 11 SNV in silico impact prediction tools were used to assess the impact of these changes. The results showed that among the 29 missense VUSs initially studied, 5 were classified as deleterious (Ala245Thr, Ala377Val, Ile678Ser, Arg746Cys and Glu797Gly) by at least 10 of 11 programs used (\(\) 80%). Among these, 2 SNVs (Ala377Val and Ile678Ser) are located in highly conserved regions of the TRPV4 gene. Although they have great importance as preliminary prediction tools, this computational approach must be complemented with other studies so that it can be concluded about the impact of the studied SNVs.